Developmental and Genotypic Variation in Leaf Wax Content and Composition, and in Expression of Wax Biosynthetic Genes in Brassica oleracea var. capitata - Laila, Rawnak; Robin, Arif Hasan Khan; Yang, Kiwoung; Park, Jong-In; Suh, Mi Chung; Kim, Juyoung; Nou, Ill-Sup (Frontiers in Plant Science, 2017)
Cuticular waxes act as a protective barrier against environmental stresses. In the present study, we investigated developmental and genotypic variation in wax formation of cabbage lines, with a view to understand the related morphology, genetics and biochemistry. Our studies revealed that the relative expression levels of wax biosynthetic genes in the first-formed leaf of the highest-wax line remained constantly higher but were decreased in other genotypes with leaf aging. Similarly, the expression of most of the tested genes exhibited decrease from the inner leaves to the outer leaves of 5-month-old cabbage heads in the low-wax lines in contrast to the highest-wax line. In 10-week-old plants, expression of wax biosynthetic genes followed a quadratic function and was generally increased in the early developing leaves but substantially decreased at the older leaves. The waxy compounds in all cabbage lines were predominately C29-alkane, -secondary alcohol, and -ketone. Its deposition was increased with leaf age in 5-month-old plants. The high-wax lines had dense, prominent and larger crystals on the leaf surface compared to low-wax lines under scanning electron microscopy. Principal component analysis revealed that the higher expression of LTP2 genes in the lowest-wax line and the higher expression of CER3 gene in the highest-wax line were probably associated with the comparatively lower and higher wax content in those two lines, respectively. This study furthers our understanding of the relationships between the expression of wax biosynthetic genes and the wax deposition in cabbage lines. Highlight: In cabbage, expression of wax-biosynthetic genes was generally decreased in older and senescing leaves, while wax deposition was increased with leaf aging, and C29-hydrocarbon was predominant in the wax crystals.